Asymptomatic Malaria Carriage in South-Western Burkina Faso: An Epidemiological Analysis - Issaka Zongo; Anthony Somé; Eric Nagaonle Some; Mamadou Ouattara; Amal Dahounto; Cédric Pennetier; Nicolas Moiroux; Roch K. Dabiré (Journal of Epidemiology and Public Health, 2021)
Background: Burkina Faso is challenged by rise in malaria incidence and insecticide and drug resistance. We investigated the prevalence of asymptomatic infection of Plasmodium falciparum. over three surveys.Subjects dan Method: We conducted repeated cross-sectional surveys in September and December 2016 and June 2017 in Diebougou health district. An initial census identified 4,028 subjects aged 6 months to 18 years. The independent variables included the age or date of birth, dependant were the area of residence, the use of bed nets, presence of not of parasites, the period of the surveys and the presence or absence of clinical signs/symptoms/fever, the gender. We used electronic case report forms for data collection, then uploaded into electronic tablets PCs, transferred to a central server. Data were analyzed with R version 3.4.3 software. Baseline charac